Fake news in oorlogstijd: Duitse mediamanipulatie en de Flamenpolitik (1914-1915) - Yammine, Bruno (Leuven University Press, 2021)
During the First World War, the German occupier tried to split Belgium internally. This was done by pursuing a Flamenpolitik, a policy aimed at scaring the Flemish, or at least the Flemish movement, against Belgium. That worked, because a small number of Flemish supporters, the so-called activists, did indeed collaborate. From the late summer of 1914, Berlin in the occupied country would incessantly bombard the Flemish movement with a large-scale media campaign. The German services, supported by their Austrian allies, mainly made use of pamphlets and the written press, not only in Belgium but also in the neutral Netherlands. In the summer of 1915 activism was a fact: an anti-Belgian Flemish nationalism, the consequences of which have been felt to date, had seen the light of day. The propaganda underlying it was so ingenious and clever that it not only convinced contemporaries, but still misleads historians even more than a century later. It is a fine example of “fake news” avant la lettre